2005
DOI: 10.1038/sj.onc.1208635
|View full text |Cite|
|
Sign up to set email alerts
|

Erythropoietin-mediated activation of JAK-STAT signaling contributes to cellular invasion in head and neck squamous cell carcinoma

Abstract: Originally characterized as a growth factor for erythrocytes, erythropoietin (EPO) is used to treat anemia and fatigue in cancer patients receiving radiation therapy and chemotherapy. EPO and the EPO receptor (EPOR) are expressed in nonhematopoietic cells and cancers. However, the role of EPO and EPOR within nonhematopoietic cancer cells remains incompletely understood. Although a recent clinical trial demonstrated worse tumor control and survival in head and neck cancer patients treated with EPO, the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
2
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(109 citation statements)
references
References 38 publications
5
99
2
3
Order By: Relevance
“…It has been repeatedly reported that enhanced JAK activity promotes cell proliferation and survival in both malignant and benign tumors (16,18,29,38,42,56). Neither RCC cell line demonstrated significant differences in proliferatiion or apoptosis, so the effect of JAK inhibition could not be determined for these phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been repeatedly reported that enhanced JAK activity promotes cell proliferation and survival in both malignant and benign tumors (16,18,29,38,42,56). Neither RCC cell line demonstrated significant differences in proliferatiion or apoptosis, so the effect of JAK inhibition could not be determined for these phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are needed with more specific antibodies and greater sample numbers to determine the prognostic significance of EpoR expression on tumors. The biological effects of Epo stimulation of tumor cells is still debated with reports of enhanced survival (8,11), proliferation (4,6,(38)(39)(40), resistance to treatment (38,41,42), tumor angiogenesis (43)(44)(45), chemotaxis (46), invasion (47)(48)(49)(50), and migration (40,46,51). Others have reported no discernible effects of Epo (52).…”
Section: Discussionmentioning
confidence: 99%
“…9). The established proliferative, angiogenetic and antiapoptotic properties of EPO indicate novel functions of the molecule in tumor progression and invasion (10). These findings are of special concern about administration of recombinant human EPO in cancer patients with anemia.…”
Section: Introductionmentioning
confidence: 93%